2021
DOI: 10.1016/j.breast.2021.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of radiation therapy combined with Polo-Like Kinase 4 (PLK4) inhibitor CFI-400945 in triple negative breast cancer

Abstract: Development of novel multimodality radiotherapy treatments in metastatic breast cancer, especially in the most aggressive triple negative (TNBC) subtype, is of significant clinical interest. Here we show that a novel inhibitor of Polo-Like Kinase 4 (PLK4), CFI-400945, in combination with radiation, exhibits a synergistic anti-cancer effect in TNBC cell lines and patient-derived organoids in vitro and leads to a significant increase in survival to tumor endpoint in xenograft models in vivo, compared to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
(17 reference statements)
2
20
0
Order By: Relevance
“…17,52,53 As a critical regulator of cancer development, PLK4 has emerged as a therapeutic target for multiple cancers. 42,43,56 PLK4 inhibitors, such as CFI-400945, 15 centrinone, 57,58 Cen-B, 27,59 YLZ-F5, 26 and YLT-11, 25 have shown anticancer effects in multiple cancers. In this study, Cen-B, a potent and highly selective PLK4 inhibitor, 60 In summary, we reported herein that keloids expressed high levels of PLK4, which induced tumor-like malignant biological behaviors in KFs, including enhanced proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,52,53 As a critical regulator of cancer development, PLK4 has emerged as a therapeutic target for multiple cancers. 42,43,56 PLK4 inhibitors, such as CFI-400945, 15 centrinone, 57,58 Cen-B, 27,59 YLZ-F5, 26 and YLT-11, 25 have shown anticancer effects in multiple cancers. In this study, Cen-B, a potent and highly selective PLK4 inhibitor, 60 In summary, we reported herein that keloids expressed high levels of PLK4, which induced tumor-like malignant biological behaviors in KFs, including enhanced proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“… 10 The PLK4 enzyme is expressed at low levels in proliferating tissues and has pleiotropic functions in processes related to mitotic progression, including cytokinesis, cell mobility, and DNA damage repair. 11 , 12 Increasing evidence indicates that PLK4 is aberrantly expressed in patient‐derived tumor samples, including colorectal cancer, 13 , 14 breast cancer, 15 , 16 bladder cancer, 17 and melanoma, 18 but is also expressed at low levels in proliferative tissues. 19 , 20 , 21 However, its expression level differs among cancers and proliferative tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLK4 inhibitors would potentiate aneuploidy and genomic instability and lead to cancer cell death (102). An in vitro experimental study showed that a novel inhibitor of PLK4, CFI-400945, in combination with radiation, exhibited a synergistic anticancer effect in TNBC cell lines and patient-derived organoids and led to a significant increase in survival to tumor endpoint in xenograft models in vivo, compared to control or single-agent treatment (44). However, overactivation of PLK4 is always correlated with centrosome amplification (CA) promoting a high risk of breast cancer (103).…”
Section: Inhibition Of Cell Cycle In Tnbcmentioning
confidence: 99%
“…Irradiated nanoparticles enhance the dose deposited locally by producing secondary electrons that add to ROS production and DNA damage within the cell [ 56 ]. Another important strategy has been to repurpose already known small molecule inhibitors and chemotherapeutic drugs to complement irradiation and function as radiosensitizers [ 59 , 60 , 61 , 62 ]. In a recent study, Speers et al analyzed the radiation responses of 21 breast cancer cell lines using a high-throughput novel drug radiosensitivity screen where the androgen receptor was identified as the optimal target for radiosensitization [ 63 ].…”
Section: Current Preclinical Tools To Evaluate Effects Of Radiation Therapymentioning
confidence: 99%